Hunting mimics and chameleons: diagnostic difficulties in atypical acute ischaemic stroke. (2nd June 2014) - Plummer, Nicholas Russell; Hari-Bhaskar, Kemparaju
Abstract : The seemingly straightforward diagnosis of acute ischaemic stroke can be complicated by the presence of conditions presenting similarly to stroke, and atypical strokes presenting with confusing and non-classical signs. We present a diagnostic quest to disentangle the effects of a number of stroke mimics from those of an underlying bilateral cerebrovascular phenomena, where with appropriate treatment of the non-stroke conditions the patient was able to make a near complete neurological recovery.